Do encanto ao desencanto, da permanência ao abandono: o trabalho docente e a construção da identidade profissional - Lemos, José Carlos Galvão (2009)
This research aimed to discuss the formation of professional identity in a context of frustration and disenchantment with the professional practice, between abandonment and permanence, including professional identity according to Claude Dubar and Antonio Nóvoa s view. Two groups of thirty-four teachers each had been selected for this research. The first, consisting of teachers who quit teaching in São Paulo state network and the second, of teachers who left the classroom to be school principals, also in the schools of state educational network, in 2006.Using semi-structured interviews, the testimony of teachers were analyzed with the intention to know the reasons that led them to leave teaching, and as such abandonment, associated with feelings of disenchantment and frustration, acts in the process of construction of the professional identity. The analysis of testimonies allowed us to identify the existence of a process that we call abandonment tactics, including tactics in the perspective reported by Michel de Certeau. Such tactics, used by many teachers as a way to stay in the profession, become euphemized forms of abandonment, an abandonment in service, which gradually develops into a permanent abandonment. We understand that the teaching professional trajectory is not linear, but marked by ruptures and continuities that give rise to meanders, decisive element in the intricate and complex process of building a professional identity, where disenchantment and frustration coexist with an idealized vision of the profession, generating a permanent conflict between the real work and the idealized one, favoring, thus, the formulation by the teacher of varying judgments about the school, the students and his own work, in the perspective identified by Pierre Bourdieu when discussing the categories of the teaching judgment. Finally, we defend the necessity of the teachers to be active subjects in the formulation of public policies that aim at the setting of the teacher to the school. Such policies must contemplate, inevitably, the improvement of working conditions and vocational development, reducing, thus, high rates of abandonment and roaming